2001
DOI: 10.1016/s0042-6989(01)00204-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual search in migraine and visual discomfort groups

Abstract: Two experiments that investigate automatic and conscious attention among migraine and visual discomfort groups are reported. The prediction of a heightened sensory sensitivity producing a processing speed advantage in migraine was tested. In Experiment 1, an automatic attention task was conducted. There was no effect of migraine group, but the high visual discomfort group responded significantly more slowly than the low visual discomfort group when 16 distractors were presented. In Experiment 2, a conscious vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 16 publications
4
48
4
Order By: Relevance
“…Wright et al 55 and Tyrrell et al 54 both used a task involving multiple targets (or, more precisely, multiple instances of the same target). This is of interest because, as we shall see, they resemble the task used in the present study, which is distinctly different from the single-target task structure used by Conlon et al [45][46][47] and Singleton and Henderson. 52,53 Singleton and Henderson 52 found that visual search performance in high-VS participants was impaired only when a high-IOVS, September 2008, Vol.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Wright et al 55 and Tyrrell et al 54 both used a task involving multiple targets (or, more precisely, multiple instances of the same target). This is of interest because, as we shall see, they resemble the task used in the present study, which is distinctly different from the single-target task structure used by Conlon et al [45][46][47] and Singleton and Henderson. 52,53 Singleton and Henderson 52 found that visual search performance in high-VS participants was impaired only when a high-IOVS, September 2008, Vol.…”
mentioning
confidence: 78%
“…53 Singleton and Henderson 52 required their subjects to locate a random three-letter target word in a matrix of three-letter distractor words in one of two configurations: visually nonstressful (10-point Arial normal font surrounded by a gray background) or stressful (10-point Arial bold font surrounded by a background of alternating horizontal black and white stripes). Singleton and Henderson, 52 in contrast to Conlon and Humphreys,47 found no difference in mean visual search response time between groups of subjects with low and high visual stress (VS) in the nonpatterned (nonstressful) task configuration. They did, however, find that introduction of the patterned (stressful) background produced a significant difference in response times between low-and high-VS groups, with the high-stress group taking longer to respond, supporting a conclusion that measurement of visual search performance provided a promising diagnostic method for identifying susceptibility to visual stress.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies described a link between visual aversion and performance in visual tasks. High visual aversion, in either migraine patients or HV, is associated with worse performance on visual tasks, such as those requiring discrimination among distractors in a visual array (35,36). Overload in the magnocellular system due to increased sensitivity to pattern and light, in the high visual discomfort group, may decrease efficiency in sustained attention to the target.…”
Section: Discussionmentioning
confidence: 99%